"Heart Rate‐Dependent" Electrocardiographic Diagnosis of Left Ventricular Hypertrophy. Issue 5 (22nd April 2012) - MADIAS, JOHN E.
<x xml:space="preserve">Abstract</x> A case is presented revealing the common phenomenon of heart rate‐dependent diagnosis of electrocardiographic (ECG) diagnosis of left ventricular hypertrophy (LVH), which consists of satisfaction of LVH criteria only at faster rates whereas ECGs with a slow heart rate do not satisfy such criteria. The mechanism of the phenomenon has been attributed to the tachycardia‐mediated underfilling of the left ventricle bringing the electrical "centroid" of the heart closer to the recording electrodes, which results in augmentation of the amplitude of QRS complexes, particularly in leads V2–V4. (PACE 2013; 36:e136–e137)